Tumor necrosis factor α– and interleukin‐1β–dependent induction of CCL3 expression by nucleus pulposus cells promotes macrophage migration through CCR1. Issue 3 (25th February 2013) - Wang, Jianru; Tian, Ye; Phillips, Kate L. E.; Chiverton, Neil; Haddock, Gail; Bunning, Rowena A.; Cross, Alison K.; Shapiro, Irving M.; Le Maitre, Christine L.; Risbud, Makarand V.
Abstract: Objective: To investigate tumor necrosis factor α (TNFα) and interleukin‐1β (IL‐1β) regulation of CCL3 expression in nucleus pulposus (NP) cells and in macrophage migration. Methods: Quantitative reverse transcription–polymerase chain reaction and immunohistochemistry were used to measure CCL3 expression in NP cells. Transfections were used to determine the role of NF‐κB, CCAAT/enhancer binding protein (C/EBPβ), and MAPK on cytokine‐mediated CCL3 promoter activity. The effect of NP‐conditioned medium on macrophage migration was measured using a Transwell system. Results: An increase in CCL3 expression and promoter activity was observed in NP cells after TNFα or IL‐1β treatment. Treatment of cells with NF‐κB and MAPK inhibitors abolished the effect of the cytokines on CCL3 expression. The inductive effect of p65 and C/EBPβ on the CCL3 promoter was confirmed through gain‐of‐function and loss‐of‐function studies. Notably, cotransfection with p50 completely blocked cytokine‐ and p65‐dependent induction. In contrast, c‐Rel and RelB had little effect on promoter activity. Lentiviral transduction with short hairpin RNA for p65 (shp65) and shIKKβ significantly decreased the TNFα‐dependent increase in CCL3 expression. Analysis of degenerated human NP tissue samples showed that CCL3, but not CCL4, expression correlated positively with the grade of tissue degeneration. Importantly, treatment of macrophages with conditioned medium of NP cells treated with TNFα or IL‐1β promoted their migration. Pretreatment of macrophages with an antagonist of CCR1, the primary receptor for CCL3 and CCL4, blocked cytokine‐mediated migration. Conclusion: Our findings indicate that TNFα and IL‐1β modulate the expression of CCL3 in NP cells by controlling the activation of MAPK, NF‐κB, and C/EBPβ signaling. The CCL3–CCR1 axis may play an important role in promoting macrophage infiltration in degenerated, herniated discs.